Fabricating Tissues In Situ with the Controlled Cellular Alignments. Issue 3 (6th January 2022) - He, Chuanjiang; Liu, Mengxue; Jiang, Deming; Wu, Jianguo; Qin, Chunlian; Liang, Tao; Wu, Pan; Han, Chunmao; Huang, Liquan; Hsia, K. Jimmy; Wang, Ping
Abstract: Tissue engineering techniques have enabled to replicate the geometrical architecture of native tissues but usually fail to reproduce their exact cellular arrangements during the fabricating process, while it is critical for manufacturing physiologically relevant tissues. To address this problem, a "sewing‐like" method of controlling cellular alignment during the fabricating process is reported here. By integrating the stretching step into the fabricating process, a static mechanical environment is created which, in turn, regulates the subsequent cellular alignment, elongation, and differentiation in the generated tissues. With this method, patterned cellular constructs can be fabricated with controlled cellular alignment. Moreover, this method shows a potent capability to fabricate physiologically relevant skeletal muscle constructs in vitro by mechanically inducing myoblast fusion and maturation. As a potential clinical application, aligned myofibers are directly fabricated onto injured muscles in vivo, which repair the damaged tissues effectively. This study shows that the "sewing‐like" method can produce engineered tissues with precise control of cellular arrangements and more clinically viable functionalities. Abstract : A "sewing‐like" method of fabricating engineered tissues in situ with the controlled cellular arrangements and more clinically viable functionalities is presented here. By integrating the "stretch" and "adhere" steps into the fabricating process, a static mechanical environment can be created, which will regulate the subsequent cellular alignment, elongation, and differentiation in the generated physiologically relevant tissues.